Enhancement of Non-Linear Generators and Calculate the Randomness Test for Autocorrelation Property - Alsaadi, Ahmed Amer; Al-Shammari, Ayad G. Naser (Iraqi Journal of Science, 2019)
In this paper, three main generators are discussed: Linear generator, Geffe generator and Bruer generator. The Geffe and Bruer generators are improved and then calculate the Autocorrelation postulate of randomness test for each generator and compare the obtained result. These properties can be measured deterministically and then compared to statistical expectations using a chi-square test.